ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒæ•™è‚²å¦é™¢æ±‰è¯ä¸“ä¸š2016å¦ç”Ÿå¯¹è¿žè¯ â€œä¸ç®¡â€ä¸Žâ€œæ— è®ºâ€çš„æŽŒæ¡æƒ…å†µåˆ†æž - Wahyuni, Rati Tri; Thamrin, Lili; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractConjunctions are an important part of Chinese grammar.Conjunction is a kind of function words, its role is to connect two words, phrases and clauses.In conjunction with the word